2022
DOI: 10.1186/s43043-022-00123-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-Mullerian hormone in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common gynecological endocrine disorders affecting up to 10% of all females in their reproductive age, and its cause of onset is still elusive. A spectrum of recent research reflected diverse associations between increased plasma level of anti-Mullerian hormone (AMH) and different clinical features of PCOS. Since AMH levels reflect the pool of growing follicles that potentially can ovulate, it can be stated that serum AMH levels can be used to assess the “functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…Our study found an inverse relationship between FSH and AMH levels and a positive trend between LH and AMH in women with PCOS, in accordance with previous studies [18,23,26,41,42]. However, despite the fact that the LH/FSH ratio has been used for establishing the diagnosis of PCOS [43,44], little is known about its predictive value for IVF outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found an inverse relationship between FSH and AMH levels and a positive trend between LH and AMH in women with PCOS, in accordance with previous studies [18,23,26,41,42]. However, despite the fact that the LH/FSH ratio has been used for establishing the diagnosis of PCOS [43,44], little is known about its predictive value for IVF outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…36,37 This could be attributed to the presence of AMH type 2 receptor (AMHR2) in both hypothalamus and pituitary organs. 38 Moreover, our results showed that leptin levels were negatively correlated with the LH/FSH ratio in women with PCOS but not in controls. These results were in line with a study 16 , whereas other studies showed the opposite results.…”
Section: Discussionmentioning
confidence: 54%
“…The samples were also taken within a narrow window of 20 days for the 1st trimester measurement and 34 days for the 2nd trimester measurement, therefore limiting the potential variability originating from differences in gestational age. The study population had limited heterogeneity as participants with PCOS or diabetes were excluded from this study, to make the data less susceptible to the effects of extreme outliers (Al Khafaji et al, 2017, Kim et al, 2016, Bhattacharya et al, 2022, Teede et al, 2019, Verdiesen et al, 2021. As such, these results cannot be generalised to women with PCOS or diabetes.…”
Section: Discussionmentioning
confidence: 99%